AN ANALYSIS OF BUSINESS DEVELOPMENT IN PLASTIC WASTE RECYCLING INTO ECO-FRIENDLY FURNITURE: A CASE STUDY OF KAMPUNG BERSERI ASTRA KEPUTIH - Susy Budi Astuti; Prasetyo Wahyudie; Agrie Pratama Harwinanto; Chaterine Eunice Michelle Naomi Koraag (Management and Sustainable Development Journal, 2026)
This study analyzed the potential and strategy for developing plastic waste recycling into eco-friendly furniture at Kampung Berseri Astra Keputih, Surabaya. Using a qualitative descriptive method, the research involved literature review, field observation, and design exploration. SWOT analysis was applied to identify internal and external factors influencing community-based business feasibility. The results showed that the area had strong potential supported by material availability, environmental awareness, and CSR programs. The study produced Eco-Block Furniture, a modular and multifunctional recycled plastic product applying knockdown and self-locking systems for practical and aesthetic purposes. Despite these advantages, challenges such as limited technical skills and public perception of recycled products remain. Continuous support and design validation are necessary to sustain implementation. In conclusion, recycling plastic waste into furniture contributes to environmental improvement and generates sustainable economic opportunities for the local community.